Implementation Analysis of the Pariaman City Regional Regulation No. 9 of 2015 concerning the Drinking Water Depot Business Permit - Roza, Melia (UI Scholars Hub, 2023)
To regulate the existence of Drinking Water Depots (DAM) in the city of Pariaman, the Pariaman City government issued Regional Regulation (Perda) Kota Pariaman No. 9 of 2015 concerning Business Permits for Drinking Water Depots. However, many depot owners do not implement these regulations. The purpose of this study was to analyze the implementation of Pariaman City Regional Regulation No. 9 of 2015 concerning Drinking Water Depot Business Permits. This research is a type of qualitative research. Data collection was carried out through in-depth interviews with informants involved in the implementation of Pariaman City Regional Regulation No. 9 of 2015 and focus group discussions (FGD) on drinking water depot owners. Selection of informants based on the principles of suitability and adequacy. The variables based on the framework of Edward III include communication, resources, disposition, and bureaucratic structure. The results of the research show that the implementation of the policy has not been implemented because the communication has not been optimal. The available resources and facilities are quite adequate, for sub-budget variables it has not gone well. Coordination has not been carried out properly, the sanctions set forth in the Regional Regulations have also not been realized optimally. Disposition related to the government's commitment to implementing policies has not been implemented. It is necessary to monitor the implementation of regional regulations and make derivative regulations related to supervision of drinking water depots, so that depots can carry out routine inspections according to what is stated in the regional regulations and make it easier for the Health Service to carry out supervision